2019
DOI: 10.1177/0144598719875272
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of gas produced from different types of biomass pellets in gasification process

Abstract: Gas from the gasification of pellets made from renewable sources of energy or from lower-quality fuels often contains a number of pollutants. This may cause technical difficulties during the gas use in internal combustion gas engines used for energy and heat cogeneration. Therefore, an adequate system of gas cleaning must be selected. In line with such requirements, this paper focuses on the characterization and comparison of gases produced from different types of biomass during gasification. The biomass teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…The elemental composition of pure spruce wood has been also observed in a study of Mikeska et al. with the following similar results: (a) 47.46% of C content, (b) 5.65% of H content, (c) 0.09% of N content, (d) 39.12% of oxygen content ( Mikeska et al, 2020 ). Compared to pure spruce sawdust, pellets have a slightly higher content of C, H, and N. Based on these results, it can be concluded that with the increasing amount of disintegrated face masks FFP2 in pellets, there was evident a significant increase of the content of C, H, and N, where C increased most significantly.…”
Section: Resultssupporting
confidence: 77%
“…The elemental composition of pure spruce wood has been also observed in a study of Mikeska et al. with the following similar results: (a) 47.46% of C content, (b) 5.65% of H content, (c) 0.09% of N content, (d) 39.12% of oxygen content ( Mikeska et al, 2020 ). Compared to pure spruce sawdust, pellets have a slightly higher content of C, H, and N. Based on these results, it can be concluded that with the increasing amount of disintegrated face masks FFP2 in pellets, there was evident a significant increase of the content of C, H, and N, where C increased most significantly.…”
Section: Resultssupporting
confidence: 77%
“…Linden leaves and maize husks had similar hydrogen content and linden leaves also similar nitrogen content. Mikeska et al stated the following contents: 47.46% for carbon, 5.65% for hydrogen, 0.09% for nitrogen and 39.12% for oxygen [6].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, new facilities with local fuels and various forms of process waste are increased. Waste is used more and more to create heat and power [34]. Biomass is derived from several sources, including Wild forest and woodland timber, Plantations of trees, Forestry byproducts, Straw, litter, and agricultural wastes are examples of agricultural residues, Sugarcane bagasse and rice husk are examples of agro-industrial waste, Waste from animals, industry, Sewerage, MSW (municipal solid waste) and Waste from food manufacturing shown in figure 7 [35].…”
Section: Biomass Energymentioning
confidence: 99%